COVID-19 pneumonia with ARDS and secondary haemophagocytic lymphohistiocytosis: a case report - Ölmez, Hasan; Tosun, Mustafa; Ünver, Edhem; Arslan Işık, Nurten (The European Research Journal, 2021)
Although most people with COVID-19 have mild to moderate symptoms; some people may experience worsened symptoms, such as pneumonia, acute respiratory distress syndrome (ARDS) and and respiratory failure. Here we reported a case of COVID-19 pneumonia with ARDS and secondary haemophagocytic lymphohistiocytosis (sHLH). A 44-year-old man presented to the emergency department with a history of cough, fever, sore throat, and muscle ache. The patient transferred to Chest Diseases Department, with a diagnosis of COVID-19 pneumonia. Oseltamivir, hydroxychloroquine, azithromycin, low molecular weight heparin (LMWH) and favipravir added to the treatment. Tocilizumab started after endotracheal intubation. In general, we saw improvement in respiratory values and vital signs. Administration of LMWH to the patient may have prevented the development of coagulopathy. In conclusion, using HFO system and using low tidal volume according to ARDS net protocol, using optimal PEEP/FiO2 ratio, paying attention to keeping driver pressures low may be beneficial for the clinical improvement of the disease.